Correlation of Self-Efficacy with Decision Making Continuing Studies in College Students at Islamic Based Universities - Defriyanto, Defriyanto; Sugiharta, Iip (Universitas Islam Negeri Raden Intan Lampung, 2020)
Decision making requires courage and confidence from individuals to be able to make decisions even though it has consequences where self-efficacy is a factor because people believe in their ability to make decisions. This study aims to determine the correlation of self-efficacy with decision making continuing studies in college students at Islamic based universities. The study population was college students of the Raden Intan State Islamic University, Lampung, with a random sampling method. The total sample of 504 college students. The instruments in this study were the scale of self-efficacy, and the scale of decision making. Data analysis using the Karl Spearman correlation test was assisted by SPSS software for Windows 23. The correlation score from the results of the study was 0.628 which showed a strong relationship between self-efficacy and respondent decision making so that the Self-Efficacy of Raden Intan College students of the State Islamic University has strong in making decisions in continuing their studies